Heat release welding flux and preparation method and application thereof

By using high-content iron oxide powder, low-content copper oxide powder and copper powder as oxidizing agents in exothermic welding, and adding molybdenum powder, tin powder, yttrium powder, chromium carbide and boron nitride, weld seams in traditional welding processes are solved. The problems of unstable quality and high porosity have achieved high melting point, low porosity and high conductivity welded joints, improving welding performance and corrosion resistance.

CN119282482AActive Publication Date: 2025-01-10BEIJING JINHEYI TECH DEV CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411826493.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-01-10
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

When connecting copper-clad steel conductors, the traditional exothermic welding process has problems such as unstable weld quality, large joint resistance and low working efficiency. The porosity of the joint after welding is high, resulting in a decrease in conductivity.

Method used

High content of iron oxide powder, low content of copper oxide powder and low content of copper powder as oxidizers, and molybdenum powder, tin powder, yttrium powder, chromium carbide and boron nitride as components B, and prepared by ball mill mechanical alloying technology Exothermic flux, optimizes welding process and joint performance.

Benefits of technology

It improves the melting point, density and conductivity of the joint after welding, reduces porosity, enhances corrosion resistance and service life, and improves welding quality and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of heat release welding, and particularly discloses a heat release welding flux and a preparation method and application thereof. The invention discloses heat release welding flux which is composed of a component A and a component B according to the weight ratio of 90-98: 2-10. The component A specifically comprises the following components in parts by weight: 50-58 parts of ferric oxide powder, 4-8 parts of copper oxide powder, 4-8 parts of copper powder, 30-40 parts of aluminum powder, 4-8 parts of molybdenum powder, 1.5-4.5 parts of tin powder and 0.5-1.5 parts of yttrium powder; the component B is specifically prepared from the following components in parts by weight: 5 to 15 parts of chromium carbide and 0.5 to 1.5 parts of boron nitride. By means of the technical scheme, the prepared heat release welding flux has excellent application performance, and the effects that after welding, a heat release welding joint is high in melting point, small in porosity, high in electric conductivity and high in corrosion resistance are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of exothermic welding, and in particular to an exothermic flux and a preparation method and application thereof. Background Art

[0002] At present, copper-clad steel conductors are widely used in power, communication and other industrial fields, and are favored for their unique electrical and physical properties. However, the traditional fusion welding process has many shortcomings when connecting such conductors, including unstable weld quality, high joint resistance and low operation efficiency. Therefore, exothermic flux, as a method that can react and generate heat for welding without external power supply, has become one of the research hotspots in the industry.

[0003] During the welding process of the exothermic flux in the prior art, the heat generated by the welding components may trigger violent chemical reactions. These reactions may produce gases, resulting in a higher porosity of the exothermic weld joint after welding, which is not conducive to the transmission of electrons and reduces the conductive efficiency of the welding head. In addition, thermal stress, internal stress concentration and microstructural defects may occur during the welding process, resulting in a decrease in the overall conductive performance of the exothermic weld joint.

[0004] Therefore, it is necessary to provide a new exothermic flux to reduce the porosity of the welded joint, thereby further improving the quality and performance of the welded joint. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides an exothermic flux and a preparation method and application thereof.

[0006] The present application provides an exothermic flux, which is composed of component A and component B in a weight ratio of 90-98:2-10; The component A specifically includes the following components in parts by weight: 50-58 parts of iron oxide powder, 4-8 parts of copper oxide powder, 4-8 parts of copper powder, 30-40 parts of aluminum powder, 4-8 parts of molybdenum powder, 1.5-4.5 parts of tin powder, and 0.5-1.5 parts of yttrium powder; The B component specifically includes the following components in parts by weight: 5-15 parts of chromium carbide and 0.5-1.5 parts of boron nitride.

[0007] The present application adopts high-content iron oxide powder + low-content copper oxide powder + low-content copper powder as the oxidant of component A of the exothermic flux, and at the same time adjusts the ratio of copper oxide powder, copper powder and aluminum powder in the flux, and adds a small amount of high-purity molybdenum powder, tin powder, yttrium powder, and uses chromium carbide and boron nitride as component B, so that the exothermic flux prepared by the present application achieves the technical effects of high melting point of the exothermic welding joint after welding, small porosity, high conductivity and strong corrosion resistance.

[0008] Compared with the traditional use of high-content copper powder or copper oxide powder as an oxidant, the inventor found in the experimental process that the use of high-content iron oxide powder, low-content copper oxide powder and low-content copper powder as the oxidant of the exothermic flux can utilize the high melting point of iron in the iron oxide powder to improve the melting point of the exothermic welding joint after welding. At the same time, low-content copper oxide powder and copper powder play a role in auxiliary oxidation. They react synergistically with iron oxide powder to further increase the heat release and optimize the welding process. This oxidant ratio also helps to improve the fluidity and wettability of the flux. The high content of iron oxide powder can make the flux easier to spread and penetrate into the gaps of the materials to be welded, improve the density of the exothermic welding joint, and the low content of copper oxide powder and copper powder helps to improve the wetting angle between the flux and the material, and improve the quality and strength of the welding joint. By precisely controlling the content and proportion of these three powders, the performance and microstructure of the welding joint can also be regulated. In addition, a high content of iron oxide powder can also improve the hardness and wear resistance of the welded joint, while properly adjusting the ratio of copper oxide powder and copper powder can optimize the conductivity and corrosion resistance of the joint.

[0009] As raw materials for exothermic flux, molybdenum powder, tin powder and yttrium powder each have unique functions: molybdenum powder, with its high melting point and high thermal conductivity, can provide stable heat output during welding, which can further increase the melting point of exothermic welded joints and ensure the high temperature stability of welded joints. Tin powder, with its good wettability and fluidity, helps the flux to spread evenly during welding and improve the quality of welded joints. Yttrium powder, as a rare earth element powder, has excellent chemical activity and antioxidant properties, which can enhance the exothermic effect of the flux and extend the service life of welded joints. Through reasonable proportioning and fine adjustment of molybdenum powder, tin powder and yttrium powder as exothermic flux raw materials, strong technical support can be provided for the welding of metal materials.

[0010] In the present application, the inventors add a small amount of high-purity chromium carbide and boron nitride with a specific particle size as component B. On the one hand, chromium carbide and boron nitride have a higher melting point and higher stability than iron, and can maintain a stable structure during welding, and can fill the tiny pores in the weld at high temperature, thereby improving the compactness of the welded joint. On the other hand, boron nitride has excellent lubricity, can fill the gaps formed between particles, increase the contact area and reaction activity with the weld metal, can more effectively reduce the surface tension of the flux, thereby enhancing the flow wettability of the flux, making the weld filling more uniform, thereby reducing the porosity. In addition, the combination of chromium carbide and boron nitride can synergistically refine the particles in the welding process, make the flux evenly distributed in the weld structure, optimize the microstructure of the welding head, and further reduce the porosity of the exothermic welded joint after welding.

[0011] In the above technical solution, chromium carbide and boron nitride improve the density of the weld joint, which helps to increase the transmission channel of electrons and reduce the scattering and obstruction of electrons during the transmission process, thereby improving the conductive efficiency of the welding head; and the high thermal conductivity of chromium carbide and boron nitride can ensure the effective transfer and distribution of heat during welding, so that the welding head can be heated quickly and evenly, which helps to eliminate thermal stress, internal stress concentration and microstructural defects that may occur during welding, thereby reducing welding defects, improving the transmission efficiency of electrons in the welding head, and then improving the overall conductive performance of the welding head.

[0012] In addition, chromium carbide and boron nitride have good chemical stability and can resist corrosion from corrosive substances such as acids and alkalis, thus protecting the welding head from damage.

[0013] Preferably, the exothermic flux consists of component A and component B in a weight ratio of 92-96:4-8.

[0014] Preferably, the component A specifically includes the following components in parts by weight: 52-56 parts of iron oxide powder, 5-7 parts of copper oxide powder, 5-7 parts of copper powder, 33-38 parts of aluminum powder, 6-8 parts of molybdenum powder, 2-3 parts of tin powder, and 0.7-1.2 parts of yttrium powder.

[0015] Preferably, the particle size of the iron oxide powder is 200-500 mesh, and the purity is ≥99.0%; the particle size of the copper oxide powder is 100-300 mesh, and the purity is ≥99.0%; the particle size of the copper powder is 100-300 mesh, and the purity is ≥99.0%; the particle size of the aluminum powder is 100-300 mesh, and the purity is ≥99.0%.

[0016] Preferably, the particle size of the molybdenum powder is 200-500 mesh, and the purity is ≥99.5%; the particle size of the tin powder is 200-500 mesh, and the purity is ≥99.5%; the particle size of the yttrium powder is 200-500 mesh, and the purity is ≥99.5%.

[0017] Preferably, the B component specifically includes the following components in parts by weight: 8-12 parts of chromium carbide, 0.7-1.2 parts of boron nitride, and 0.8-1.2 parts of tungsten oxide.

[0018] This application utilizes the semiconductor properties of tungsten oxide, adds an appropriate amount of tungsten oxide to the flux B component, and uses it in combination with the reinforcing materials chromium carbide and boron nitride. Through the synergistic effect between the materials, more conductive channels can be formed during the welding process, thereby further improving the conductivity of the welding head; the addition of tungsten oxide may help improve the microstructure of the welding head, making the weld joint more uniform and dense. This structural improvement helps the smooth transmission of electrons, thereby improving the conductive efficiency of the welding head.

[0019] Preferably, the B component specifically includes the following components in parts by weight: 6-14 parts of chromium carbide, 0.6-1.4 parts of boron nitride, and 0.7-1.3 parts of tungsten oxide.

[0020] Preferably, the particle size of the boron nitride is 400-800 meshes, and the purity is ≥99.99%; the particle size of the chromium carbide is 100-800 meshes, and the purity is ≥99.99%; the particle size of the tungsten oxide is 100-300 meshes, and the purity is ≥99.99%.

[0021] In a second aspect, the present application provides a method for preparing the above-mentioned exothermic flux, characterized in that the method specifically comprises sequentially performing the following steps: According to the raw material ratio of component A, iron oxide powder, copper oxide powder, copper powder, aluminum powder, molybdenum powder, tin powder, and yttrium powder are weighed respectively, and the powders of each component are stirred evenly by a three-dimensional stirrer to form component A; According to the raw material ratio of component B, weigh chromium carbide, boron nitride and tungsten oxide respectively, mix them evenly and put them into a ball mill, add steel balls at a ball-to-material ratio of 6-8:1, ball mill at 200-400r / min, pass through a 500-mesh sieve to form component B; The exothermic flux is obtained by mixing the powders of component A and component B uniformly with a three-dimensional mixer.

[0022] Component B is prepared by ball milling mechanical alloying technology. The high-speed impact and shear force during the ball milling process cause severe plastic deformation and cold welding between the powders, thereby promoting atomic diffusion and alloying reaction between the powders; after mixing with component A, an exothermic flux with exothermic welding performance can be obtained.

[0023] In a third aspect, the present application provides the use of the above-mentioned exothermic flux in copper-clad steel welding for power grounding engineering.

[0024] In summary, the technical solution of this application has the following effects: Compared with the traditional high-content copper technical solution, the present application adopts high-content iron oxide powder + low-content copper oxide powder + low-content copper powder as the oxidant of component A of the exothermic flux, and at the same time adjusts the ratio of copper oxide powder, copper powder, and aluminum powder in the flux, and adds a small amount of high-purity molybdenum powder, tin powder, yttrium powder, and uses chromium carbide, boron nitride, and tungsten oxide as component B. The exothermic flux prepared by the present application achieves the technical effects of high melting point, small porosity, high conductivity and strong corrosion resistance of the exothermic welding joint after welding. DETAILED DESCRIPTION

[0025] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application. Example Examples 1-9

[0026] Examples 1-9 respectively provide an exothermic flux and a preparation method thereof.

[0027] The difference between the above embodiments is that the amounts of the raw material components in component A of the exothermic flux are different, as shown in Table 1.

[0028] The preparation method of the exothermic flux in the above embodiment is: According to the raw material ratio of component A, iron oxide powder, copper oxide powder, copper powder, aluminum powder, molybdenum powder, tin powder, and yttrium powder are weighed respectively, and the powders of each component are stirred evenly by a three-dimensional stirrer to form component A; According to the raw material ratio of component B, 10 parts by weight of chromium carbide, 1 part by weight of boron nitride and 1 part by weight of tungsten oxide were weighed respectively, mixed evenly and put into a ball mill, steel balls were added at a ball-to-material ratio of 7:1, ball milled at 300 r / min, and passed through a 500-mesh sieve to form component B; The A component and the B component are mixed uniformly in a weight ratio of 94:6 by a three-dimensional mixer to obtain an exothermic flux.

[0029] Table 1 Amount of each raw material component in component A of the exothermic flux in Examples 1-9 Examples 10-13

[0030] Examples 10-13 respectively provide an exothermic flux and a preparation method thereof.

[0031] The difference between the above embodiment and embodiment 2 is that the amount of each raw material component in component B is different, as shown below.

[0032] In Example 10: According to the raw material ratio of component B, 5 parts by weight of chromium carbide and 1.5 parts by weight of boron nitride are weighed respectively, mixed evenly and put into a ball mill, steel balls are added at a ball-to-material ratio of 7:1, and component B is formed by ball milling at 300 r / min.

[0033] In Example 11: According to the raw material ratio of component B, 15 parts by weight of chromium carbide, 0.5 parts by weight of boron nitride, and 1.5 parts by weight of tungsten oxide are weighed respectively, mixed evenly, and put into a ball mill, and steel balls are added at a ball-to-material ratio of 7:1, and ball milling is performed at 300 r / min to form component B.

[0034] In Example 12: According to the raw material ratio of component B, 8 parts by weight of chromium carbide, 1.2 parts by weight of boron nitride, and 0.8 parts by weight of tungsten oxide are weighed respectively, mixed evenly, and put into a ball mill, and steel balls are added at a ball-to-material ratio of 7:1, and ball milling is performed at 300 r / min to form component B.

[0035] In Example 13: According to the raw material ratio of component B, 12 parts by weight of chromium carbide, 0.7 parts by weight of boron nitride, and 1.2 parts by weight of tungsten oxide are weighed respectively, mixed evenly, and put into a ball mill, and steel balls are added at a ball-to-material ratio of 7:1, and ball milling is performed at 300 r / min to form component B.

[0036] The other process parameters in the above embodiment are the same as those in embodiment 2. Examples 14-17

[0037] Examples 14-17 respectively provide an exothermic flux and a preparation method thereof.

[0038] The difference between the above embodiment and embodiment 2 is that the weight ratio of component A to component B is different, as shown below.

[0039] In Example 14: the weight ratio of component A to component B is 90:10.

[0040] In Example 15, the weight ratio of component A to component B is 92:8.

[0041] In Example 16, the weight ratio of component A to component B is 96:4.

[0042] In Example 17, the weight ratio of component A to component B is 98:2.

[0043] The other process parameters in the above embodiment are the same as those in embodiment 2. Comparative Example Comparative Examples 1-7

[0044] Comparative Examples 1-7 respectively provide an exothermic flux and a preparation method thereof.

[0045] The difference between the comparative example and Example 2 is that the amounts of the raw material components in component A in the exothermic flux are different, as shown in Table 2.

[0046] Table 2 Amount of each raw material component in component A of the exothermic flux in comparative examples 1-7 Comparative Examples 8-10

[0047] Comparative Examples 8-10 respectively provide an exothermic flux and a preparation method thereof.

[0048] The differences between the above comparative example and Example 2 are specifically as follows.

[0049] In Comparative Example 8: According to the raw material ratio of component B, 20 parts by weight of chromium carbide, 0.2 parts by weight of boron nitride, and 2 parts by weight of tungsten oxide were weighed respectively, mixed evenly and put into a ball mill, steel balls were added at a ball-to-material ratio of 7:1, and component B was formed by ball milling at 300 r / min.

[0050] In Comparative Example 9: According to the raw material ratio of component B, 10 parts by weight of silicon carbide powder, 1 part by weight of boron nitride, and 1 part by weight of chromium oxide powder were weighed respectively, mixed evenly and put into a ball mill, steel balls were added at a ball-to-material ratio of 7:1, and component B was formed by ball milling at 300 r / min.

[0051] In Comparative Example 10: the weight ratio of component A to component B is 85:15.

[0052] The other process parameters in the above comparative example are the same as those in Example 2. Performance testing

[0053] The exothermic flux prepared in the examples and comparative examples was used to perform exothermic welding on copper-clad steel with a thickness of 0.6 mm, and then the performance of the obtained exothermic welded joint was tested as follows: (1) Melting point: The melting point of the exothermic weld joint is tested by differential thermal analysis, and the temperature at which melting begins is taken as the melting point.

[0054] (2) Porosity: The microstructure of the joint was analyzed using a scanning electron microscope, and the proportion of porosity was calculated.

[0055] (3) Resistivity: The resistivity of the copper wire after welding with an exothermic flux is determined using the method specified in GB / T351-1995 "Method for measuring the resistivity of metallic materials".

[0056] (4) Corrosion resistance: An electrochemical corrosion test was carried out on the obtained exothermic weld joint in a soil environment using an electrochemical workstation. The corrosion current was obtained by analyzing the polarization curve, and the average corrosion rate was calculated based on the corrosion current.

[0057] Test results: as shown in Table 3.

[0058] Table 3 Application performance test results of the exothermic flux prepared in the examples and comparative examples

[0059] Combined with Table 3, by comparing the application performance test results of the exothermic flux in Examples 1-17 and Comparative Examples 1-10, it can be seen that the exothermic flux prepared by the technical solution provided by the present application is used to perform exothermic welding on the copper-clad steel, and then the melting point of the obtained exothermic welded joint is 1230-1289°C, which is higher than the melting point of the copper layer of the copper-clad steel of 1083°C. The high melting point can make the exothermic welded joint have high thermal stability; the obtained exothermic welded joint has no cracks, a porosity of 3.85-6.04%, and a dense high organization that helps to improve the corrosion resistance and electrical properties of the exothermic welded joint; the resistivity of the exothermic welded joint is 0.023-0.045Ω·mm 2 ·m -1, high conductivity helps to ensure the electrical performance of the exothermic welding joint; the average soil corrosion rate is 0.0031-0.0051mm / a, and high corrosion resistance helps to extend the service life of the joint.

[0060] In Comparative Example 1, low-content iron oxide powder + high-content copper oxide powder + high-content copper powder are used as component A, and the resulting exothermic welding joint has a high melting point, a large porosity, and poor corrosion resistance. In Comparative Example 2, excessively high-content iron oxide powder + low-content copper oxide powder + low-content copper powder are used as component A, and the resulting exothermic welding joint has a large porosity, poor conductivity and corrosion resistance. In Comparative Example 3, a small amount of iron powder is added instead of iron oxide powder, and the resulting exothermic welding joint has a large porosity and poor corrosion resistance. In Comparative Example 4, the content of copper oxide powder is low and the content of copper powder is high, in Comparative Example 5, the content of copper oxide powder is high and the content of copper powder is low, in Comparative Examples 6-7, the amounts of molybdenum powder, tin powder, and yttrium powder are not matched, and the comprehensive performance of the resulting exothermic welding joint is poor. In Comparative Example 8, the type or amount of component B is not matched, and in Comparative Example 10, the amount ratio of component A to component B is not matched, and the comprehensive performance of the resulting exothermic welding joint is poor.

[0061] In contrast, the present application uses high-content iron oxide powder + low-content copper oxide powder + low-content copper powder as the oxidant of component A of the exothermic flux, and at the same time adjusts the ratio of copper oxide powder, copper powder, and aluminum powder in the flux, and adds a small amount of high-purity molybdenum powder, tin powder, yttrium powder, and uses chromium carbide, boron nitride, and tungsten oxide as component B. The exothermic flux prepared by the present application achieves the technical effect of a higher melting point, smaller porosity, higher conductivity, and stronger corrosion resistance of the exothermic welding joint after welding.

[0062] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. An exothermic flux, characterized in that: It is composed of component A and component B in a weight ratio of 90-98:2-10; The component A specifically includes the following components in parts by weight: 50-58 parts of iron oxide powder, 4-8 parts of copper oxide powder, 4-8 parts of copper powder, 30-40 parts of aluminum powder, 4-8 parts of molybdenum powder, 1.5-4.5 parts of tin powder, and 0.5-1.5 parts of yttrium powder; The B component specifically includes the following components in parts by weight: 5-15 parts of chromium carbide and 0.5-1.5 parts of boron nitride.

2. The exothermic flux according to claim 1, characterized in that The invention is composed of component A and component B in a weight ratio of 92-96:4-8.

3. The exothermic flux according to claim 1, characterized in that The component A specifically includes the following components in parts by weight: 52-56 parts of iron oxide powder, 5-7 parts of copper oxide powder, 5-7 parts of copper powder, 33-38 parts of aluminum powder, 6-8 parts of molybdenum powder, 2-3 parts of tin powder, and 0.7-1.2 parts of yttrium powder.

4. The exothermic flux according to claim 1, characterized in that The particle size of the iron oxide powder is 200-500 mesh, and the purity is ≥99.0%; the particle size of the copper oxide powder is 100-300 mesh, and the purity is ≥99.0%; the particle size of the copper powder is 100-300 mesh, and the purity is ≥99.0%; the particle size of the aluminum powder is 100-300 mesh, and the purity is ≥99.0%.

5. The exothermic flux according to claim 1, characterized in that The particle size of the molybdenum powder is 200-500 mesh, and the purity is ≥99.5%; the particle size of the tin powder is 200-500 mesh, and the purity is ≥99.5%; the particle size of the yttrium powder is 200-500 mesh, and the purity is ≥99.5%.

6. The exothermic flux according to claim 1, characterized in that The B component specifically includes the following components in parts by weight: 5-15 parts of chromium carbide, 0.5-1.5 parts of boron nitride, and 0.5-1.5 parts of tungsten oxide.

7. The exothermic flux according to claim 6, characterized in that The B component specifically includes the following components in parts by weight: 6-14 parts of chromium carbide, 0.6-1.4 parts of boron nitride, and 0.7-1.3 parts of tungsten oxide.

8. The exothermic flux according to claim 6, characterized in that The particle size of the boron nitride is 100-300 mesh, and the purity is ≥99.99%; the particle size of the chromium carbide is 100-300 mesh, and the purity is ≥99.99%; the particle size of the tungsten oxide is 100-300 mesh, and the purity is ≥99.99%.

9. The method for preparing the exothermic flux according to any one of claims 1 to 8, characterized in that: Specifically, the following steps are performed in sequence: According to the raw material ratio of component A, iron oxide powder, copper oxide powder, copper powder, aluminum powder, molybdenum powder, tin powder, and yttrium powder are weighed respectively, and the powders of each component are stirred evenly by a three-dimensional stirrer to form component A; According to the raw material ratio of component B, weigh chromium carbide, boron nitride and tungsten oxide respectively, mix them evenly and put them into a ball mill, add steel balls at a ball-to-material ratio of 6-8:1, ball mill at 200-400r / min, pass through a 500-mesh sieve to form component B; The exothermic flux is obtained by mixing the powders of component A and component B uniformly with a three-dimensional mixer.

10. Use of the exothermic flux as claimed in any one of claims 1 to 8 in welding copper-clad steel for power grounding engineering.

Citation Information

Patent Citations

  • Copper-clad steel / copper grounding grid heat release welding flux with high safety

    CN101637853A

  • Heating welding flux of copper-coated steel / steel grounding network

    CN102198570A

  • Heat-releasing welding flux for iron-base copper-clad steel grounding grid

    CN103639613A

  • Welding powder formula for welding flat belt type copper-coated steel grounding body

    CN112077481A

  • Copper-clad steel exothermic welding flux as well as preparation method and application thereof

    CN112475590A